Dynamics of vector competence for dengue virus type 2 in rural and urban populations of Aedes albopictus: implications for infectious disease control - Jehangir Khan; Muhammad Adil; Zhang Junyan; Dongjing Zhang; Yidong Deng; Zhiyue Lv; Tao Chen (Parasites & Vectors)
Abstract Background Understanding the intrinsic factors that influence mosquito vector competence (VC) to pathogens is crucial for assessing the risk of disease transmission in both rural and urban environments. We assessed the VC of Aedes albopictus mosquitoes from urban (dengue-endemic) and rural (dengue-free) areas in Guangzhou, China, for dengue virus-2 (DENV-2), while also examining intrinsic factors such as Wolbachia and immune-related gene expression influencing VC. Methods Adult females of rural, urban, and laboratory (control) populations of Ae. albopictus were orally exposed to a freshly prepared suspension of the DENV-2 New Guinea C strain (GenBank: AF038403.1), with a final titer of 1 × 107 plaque-forming units (PFU)/ml, for a period of 60 min. Three different bioassays (B1–B3) were conducted on 60 mosquitoes per population: B1 at 7 days post-exposure (dpe) to assess viral infection in the mosquito midgut, and B2 and B3 at 14 dpe to evaluate viral dissemination in the carcass and transmission via saliva. The mosquito samples were processed for total RNA and DNA extraction. RNA was subsequently analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) to quantify viral load and measure the expression of immune-related genes, while DNA was assessed via quantitative PCR (qPCR) to determine Wolbachia density (wAlbA and wAlbB) and the rps6 gene. Results At 7 dpe, virus proliferation in rural mosquitoes was similar to that in urban mosquitoes (P = 0.10). By 14 dpe, rural mosquitoes showed a significantly lower status of virus dissemination (P < 0.04) and transmission (P < 0.012). Wolbachia (−0.12 < r < −0.92) and immune effectors (−0.025 < r < −0.568) were negatively correlated with DENV in all mosquitoes, with more negative values indicating a stronger inverse relationship. The wAlbA and wAlbB strains exhibited similar densities across all the mosquito populations, with wAlbB revealing a slightly greater abundance in rural mosquitoes, although the difference was not significant. Elevated Relish 2 (Rel2), defensin A (DefA), and the signal transducers and activators of transcription (STAT) levels indicate activation of the Toll and JAK-STAT pathways, contributing to resistance against DENV replication and reduced VC in rural mosquitoes. Conclusions This study indicates that rural Ae. albopictus mosquitoes may possess intrinsic barriers limiting their VC for DENV-2, offering valuable preliminary insights into VC across geographically distinct populations. However, further research across a broader range of urban and rural locations is needed to validate these findings and better understand the local factors influencing VC. Such insights are vital for public health, as they can help prioritize locations for dengue surveillance and effective vector control. Future studies should investigate the roles of intestinal microflora and immune pathways across diverse mosquito populations to better understand these dynamics and improve our knowledge of mosquito-borne disease transmission in different environments. Graphical Abstract